Para além dos limites dos jogos eletrônicos: ampliando as possibilidades educacionais - Teixeira, Yves de Andrade e (2017)
In this work we briefly present the concept of Game, followed by the the history of Videogames. Posteriorly, we present a quantitative analysis of the academic works published in CAPES platform, searched by the keywords "Eletronic Game" and "Videogame". Thus, we demonstrate the number of productions related to the referred terms and the main scientific areas which addressed about the issue. From this, our objective consisted in elaborate the following categorization: Videogames as impossibility: The violence and consumption/alienation through the Culture Industry, based on the theoretical reference of Psychoanalysis and the Critical Theory; and the Educational Possibilities of the Videogames: Musicality, symbol, Ritual and Ethic, taking us on basis of the theoretical reference of Phenomenology of Husserl (1980) and, still, appealing to the Adornian method of the constellation of concepts, present in his work Negative Dialetics (ADORNO, 2009). In this sense, our intent was to make explicit that the Videogames include themselves, while object, the educative potentiality, which can be subjectively signified as positives in relation to subject and object.